Optimization of product function for handicapped purpose usage - Mohd Fazren Asraf, Abdull Talib (2009)
This thesis elaborates about methods done to optimize product function for handicapped purpose usage. The objectives of this project are to identify suitable general product for the usage of handicap people, redesign and analyze the product to optimize the usage for handicapped usage and to simulate and the design of the product. This thesis gathered information from previous research and study as a guideline to generate suitable concepts for flexible cooker. The concept undergoes several processes in order to determine the best suit concept for both handicap and normal user. Based from the process before, several sketches was sketched on the plain paper and transferred into three-dimensional using Computer-Aided Design tool which is SolidWork. The concept then was chosen using appropriate selection procedure. The concept selection method used is concept screening. After the concept was chosen, the design was analyzed using compatible Finite Element Analysis (FEA) software with different materials. The software used in the project is FEMPRO. Finally, the conclusion and recommendation was stated.